Perception of Consumer Rights among the College Students: A Case of Tikapur Municipality - Rawal, Dhabindra (Contemporary Research: An Interdisciplinary Academic Journal, 2019)
This study aims at examining consumes’ perception towards marketing practices and consumer rights in Tikapur Municipality, Kailali based on an empirical study of college students in connection to John Kennedy’s bill of four consumer rights, namely, the right to safety, the right to be informed, the right to choose, and the right to be heard. This study depends on a convenience sample of 60 students selected from Management, Education and Humanities faculties studying in graduate level at Tikapur Multiple Campus and Birendra Vidhya Mandir Campus at Tikapur, with a structured questionnaire to measure consumer attitudes regarding the four basic consumer rights, utilizing a fivepoint Likert Scale for measurement. The overall findings communicate that the current consumers’ attitudes towards marketing practices related to protection of consumer rights is low favorable, indicating that more work will be needed for improvement. This study explores the status of perceived consumer rights for the first time in study area. It suggests marketers and public policy makers to pay more attention to the current status of consumer rights, and formulate more useful legislations with implications for better business strategies.